Predictors of adverse outcome of severe infections in critically ill children - K. V. Pshenisnov; Yu. S. Aleksandrovich; K. Yu. Krasnoselskiy; V. A. Kaziakhmedov; A. I. Konev; M. U. Kozubov (Вестник анестезиологии и реаниматологии)
Background. Assessing the probability of an adverse outcome of severe infections and sepsis in children in order to timely correct treatment is one of the most acute problems of resuscitation and intensive care.   The ojective was to identify predictors of the adverse outcome of severe infections and sepsis in children upon admission to ICU.   Materials and methods. Design – a retrospective cohort multicenter uncontrolled study. 180 children with a severe course of infectious diseases and sepsis were examined. The mean age of the patients was 1.3 (0.5–4.1) years, boys were 94 (52.2 %) patients and girls were 86 (47.7 %) patients. Signs of shock at admission were detected in 100 (55.6 %) children. The PEMOD score on the first day of treatment in ICU was 5.0 (40–8.0) points. The duration of treatment in ICU was 8.6 (1–83) days. Depending on the outcome of the disease, all patients were divided into two groups: groupI – «recovery», group II – «death».   Results. Significant differences depending on the outcome of the disease were characteristic of clinical and laboratory signs such as mean bloodpressure, base deficiency, PEMOD score, concentration of total protein, albumin and lactate in the blood. Mean blood pressure below 60 mmHg., base deficiency > [–8.4] mmol/L, plasma lactate greater than 3.3 mmol/L, serum albumin less than 30 g/L and PEMOD > 7 on ICU admission indicate a high probability of death. The magnitude of the base deficiency has the maximum sensitivity (87.5 %) and specificity (61.3 %) to predict outcome on ICU admission.   Conclusion. The severity of the condition of children with a severe course of infectious diseases and sepsis upon admission to ICU is due to the phenomena of systemic hypoperfusion, hypoxia and metabolic disorders against the background of hypoalbuminemia.